SISTEM PAKAR UNTUK MENDIAGNOSIS KECERDASAN MAJEMUK MENGGUNAKAN METODE FUZZY EXPERT SYSTEM - Setiawan, Nanda Surya; Jusak, Jusak; Lemantara, Julianto (Jurnal JSIKA, 2013)
Abstract:.”In Indonesia, it is very minimal knowledge of parents about how to view and directing interests and talents of children, especially in the regions where development is less concern by the government. Based on research, at school was found approximately 40% of gifted children, but their perform can’t equivalent with their actual capacity (Lucy, 2010). Consequently, many talented children classified as underachievers although they have highly skilled. This conditons make ineffective growth of child and their big talent can’t visible earlier. Their parents and their teacher must knowing the highest intelligence of children from an early age and then quality of education can be improved faster. So this software expected to help an elementary school teacher work together with their parents to diagnose their intelligence more accurately and quickly with view from their hobbies. This software is also expected to showing some information to teachers as educators and parents for how to assist growth of their children based from their intelligence.”